Research and Practice on the Practical Teaching System of Architecture Specialty in Local Universities Under the Background of Application-Oriented Talents Training (Journal of Education and Development, 2022)
With the continuous development of China's construction industry, China's demand for architectural professionals is increasing, which also promotes the great development of architectural education. In the practical teaching of architecture major in local universities, there are still some problems: classroom theory cannot be combined with practical courses, teaching mode is too single, teaching lacks flexibility and characteristics, teaching content lags behind, students have few opportunities to practice learning in society and enterprises, and their participation is not high. Through the reform and practice of practical teaching system, the characteristic architecture education of independent colleges is developed to improve the practical and hands-on design ability of architecture students.